(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
A new and well-preserved fossil whip scorpion (Arachnida: Uropygi: Thelyphonida) is described from the Late Carboniferous of the Carnic Alps, Friuli, Italy. It is referred to Parageralinura marsiglioi n. sp. The new specimen is the first Carboniferous arachnid to be described from mainland Italy and is possibly the youngest Palaeozoic thelyphonid.